How Is Talaq Validity Determined Under Mental Disorders? A Transdisciplinary Islamic Family Law Perspective - Ahmad Zaki Mujahid; Syafuri Syafuri; Oom Mukarromah; Sayehu Sayehu; Resti Septiani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This study aims to examine how the validity of divorce (talaq) is determined when the husband experiences a mental disorder from a transdisciplinary Islamic family law perspective. This qualitative normative legal research employs conceptual, case, and transdisciplinary approaches by integrating Islamic jurisprudence, qawaid al-fiqhiyyah (Islamic legal maxims), maqasid al-shariah (objectives of Islamic law), clinical psychology, psychiatry, and Islamic family law and judicial perspectives. Data were obtained through library research involving classical and contemporary fiqh literature, scientific journals, the Compilation of Islamic Law, mental health literature, and selected religious court decisions concerning mental disorders in divorce cases. The findings indicate that the validity of talaq cannot be determined solely from its verbal pronouncement but requires consideration of the husband's consciousness, reasoning ability, intention, voluntariness, and legal capacity at the time of pronouncement. Mental disorders, including bipolar disorder, schizophrenia, borderline personality disorder, and major depressive disorder, may affect aql (reason), iradah (will), and ahliyyah (legal capacity), although their effects vary according to clinical severity, symptoms, and temporal conditions. Mental disorder therefore does not automatically invalidate talaq. This study concludes that its validity requires a contextual and case-sensitive assessment integrating Islamic legal principles, clinical and psychiatric assessment, judicial considerations, and maqasid al-shariah. The study contributes a transdisciplinary framework for determining legal capacity and talaq validity while protecting individual rights, marital interests, and family welfare.